iTVnews:Uma Ferramenta para Construção de Aplicações Telejornalísticas em TVDI - Sousa, Marcelo Fernandes de (2010)
On the TV news we see every day a lot of information. This requires hard work from TV news teams, since the time between the creation of content and its broadcasting decreases over the years. Today, to create interactive applications, journalists need support from the IT team and this can delay the development of interactive material. The goal of this work is to make possible automatically creation of Interactive Digital Television journal applications (voting, quiz, chats, etc.). Thus, we present the tool called iTVnews that offers a computer environment that abstracts the complexity of programming these applications. The tool focuses on the language of the journalists domain.